The fundamental differences between the Islamic and secular conceptions of knowledge: an exposition of the themes of the first revelation to Prophet Muhammad (Peace Be Upon Him) - Sulaiman, Kabuye Uthman (2015)
This paper describes the concept of knowledge with reference to the themes of the first revelation to Prophet Muhammad (peace be upon him). It is divided into seven sections elucidating the Lordship (sovereignty) of Allah, the foremost requirement in the pursuit of knowledge, the origin of knowledge, the value of knowledge, the ultimate objective of knowledge, the value of the pen and the key to the acquisition of knowledge. The primary purpose of this study is twofold; to highlight the fundamental differences between the Islamic and secular conceptions of knowledge; and to show the cohesion of knowledge and deeds, role of knowledge in the formation of civilization, inseparability of knowledge and God, and the necessary connection between senses and intellect. The main argument of the paper is that reading in the name of Allah is the key to acquisition of knowledge and the distinguishing characteristic of knowledge acquisition in Islam. Also knowing one’s origin and one’s place in the universe is one of the goals of knowledge acquisition in Islam. The paper contends that the first revelation to Prophet Muhammad (peace be upon him) played a significant role in the intellectual development in Arabia and beyond. It takes iqra’ (the command to read/seek knowledge) as the central force in the emergence of Islamic civilization and a key factor in the subsequent emergence of the Western civilization. The study concludes with summation of the discussion and recommendations.